Successful identification of culprit drugs of perioperative anaphylaxis by repeated skin testing after negative first skin tests in a patient with a long distant history of perioperative anaphylaxis - Wasurat Sungworn (Elsevier, 2021)
Background: Perioperative anaphylaxis is a severe immediate hypersensitivity reaction to drugs administered in immediate temporal association to surgical procedures. The European Academy of Allergy and Clinical Immunology recommends allergologic tests be performed within the golden period of between 1 and 4 months after the date of the event to avoid false negatives. Nonetheless, many obstacles prevent patients from receiving diagnostic tests within the recommended time frame. Case presentation: A 39-year-old male with congenital glaucoma had a history of multiple episodes of perioperative anaphylaxis since the age of 1 year including generalized urticaria, bronchospasm, cyanosis, and hypotension. Because the sequence of events was unclear due to incomplete documentation of operations and the destruction of medical records, the allergists tested different perioperative drugs on the patient. Although the first test results were all negative, repeated tests at 6 weeks were positive for morphine and ketamine. We identified more than one causative drug at the second round of skin tests. Using recommended skin test concentrations, negative skin tests in 5 control subjects could support the validity of the second test. The patient underwent sinus surgery in the next 3 months after the second skin test using propofol, midazolam, sevoflurane, chlorhexidine, and cefazolin without any anaphylactic reactions. Conclusions: Repeated skin tests after negative results of the first tests may identify the causative drugs, thus providing optimal patient safety, and should be considered under the physician's discretion together with consideration of the severity of the allergic symptoms, time interval from last reactions, and the patient's consent.